Integrative Transcriptomics and Metabolomics Reveal the Key Metabolic Pathways in Endophyte-Infected Rice Seedlings Resistance to Na2CO3 Stress - Xinnan Wang; Yanan Li; Hefei Sun; Lihong Zhang; Xuemei Li (Plants)
Soil saline-alkalization is a key factor affecting rice growth and physiological metabolism, which leads to reduced yields. Endophyte EF0801 significantly promoted growth and improved its saline-alkali resistance. We investigated growth parameters and physiological indices of endophyte EF0801-infected and control rice seedlings under sodium carbonate (Na2CO3) stress. The results showed that endophyte-infected rice seedlings showed plant height increase by 1.25-fold, root length shortening by 0.79-fold, sucrose synthase (SS), sucrose phosphosynthase (SPS), hexokinase (HXK), and α-glucosidase (α-GC) activities increased by 0.15-fold, 0.29-fold, 0.06-fold, and 1.45-fold, respectively, and β-glucosidase (β-GC) activity decreased by 0.12-fold. Utilizing gas chromatography and mass spectrometry (GC-MS) technology and RNA sequencing (RNA-seq) technology, we identified 419 differentially expressed genes (DEGs) and 37 differentially accumulated metabolites (DAMs). Comprehensive enrichment analysis of DAMs and DEGs showed that 6 DEGs and 6 DAMs were strongly correlated with the mitigating effects of endophytes on rice leaves under Na2CO3 treatment, highlighting the co-enrichment in starch and sucrose metabolism, as well as alanine, aspartate, and glutamate metabolism. The gene encoding HXK was found to be upregulated in endophyte-infected rice seedlings under Na2CO3 stress. HXK plays a key role in the conversion of fructose and glucose to fructose 6-phosphate (F-6-P) and glucose 6-phosphate (G-6-P), which are important intermediates in cellular energy metabolism and glycolytic pathways, providing energy and biosynthesis of precursor substances. Our findings provide a potential perspective for unraveling the molecular response of endophyte-mediated saline-alkali resistance in rice leaves and a theoretical rationale for exploring the mechanisms of growth-promoting effects by endophytes.